Clinical and sociodemographic profile of children with cerebral palsy participants in a psychomotor stimulation program at a rehabilitation hospital - Teixeira, Tiago de Matos; Sousa, Thalita Costa de; Assunção, Jeane Rodella (Research, Society and Development, 2023)
Cerebral Palsy (CP) can be defined as a group of movement and posture disorders, causing limitation in the individual's execution of actions, which are attributed to non-progressive disorders that occurred in fetal or infant brain development. There are several possibilities for intervention in children with CP, seeking to improve function, among them Psychomotricity. This can be defined as the relationship between thought and action, involving emotion. Given the importance of using psychomotor practice in children with CP, this study will provide important information for understanding the profile of these patients and, from there, outlining new stimulation possibilities for this population. Objective: To analyze the clinical and sociodemographic profile of children with CP who participated in a psychomotor stimulation program at a physical rehabilitation hospital. Method: This is a document analysis, with descriptive statistics of children with CP who participated in Psychomotor Stimulation groups in the SARAH Network of Rehabilitation Hospitals - Salvador/BA Unit, between 2016 and 2020. Results: In this study, it was observed predominance of male CP patients, aged between 3 and 5 years, from Salvador, GMFCS level I, spastic hemiplegic type. Conclusion: The findings of this study are relevant for the academic society, considering the scarcity of studies involving CP and Psychomotricity. In addition, they point to a new possibility of intervention by health professionals, characterizing an important part of the rehabilitation process of these individuals.